108k views
4 votes
Simplify the expression below. Write your answer with only positive exponents.

(a^3b^2c/a^5c^2)(a^2b/c^4)

User TKumar
by
6.0k points

1 Answer

2 votes

Answer:

The expression
\left((a^3b^2c)/(a^5c^2)\right)\left((a^2b)/(c^4)\right) is equal to
(b^3)/(c^5)

Explanation:

We have the following expression


\left((a^3b^2c)/(a^5c^2)\right)\left((a^2b)/(c^4)\right)

To simplify the expression you need to:

The left side of the expression is
(a^3b^2c)/(a^5c^2)=(b^2)/(a^2c) because


\mathrm{Apply\:exponent\:rule}:\quad (x^a)/(x^b)=(1)/(x^(b-a))


(a^3)/(a^5)=(1)/(a^(5-3)) and
(c)/(c^2)=(1)/(c^(2-1))


(b^2)/(c^(2-1)a^(5-3)) = (b^2)/(a^2c)

Next,


(a^2b)/(c^4)\cdot (b^2)/(a^2c)


\mathrm{Multiply\:fractions}:\quad (a)/(b)\cdot (c)/(d)=(a\:\cdot \:c)/(b\:\cdot \:d)


(b^2a^2b)/(a^2cc^4)


\mathrm{Cancel\:the\:common\:factor:}\:a^2


(b^2b)/(cc^4)

We know that
b^2b=b^3 and
cc^4=c^5

Therefore
(b^3)/(c^5)

User Kalpesh Panchal
by
5.6k points